Mechanical analysis of a portal steel frame when subjected to a post-earthquake fire - Merouani, Mohammed Redha (2020)
Although current design code can manage the separate action of a fire or an earthquake, which causes a significant threat to the human life and to the integrity of the structures, the dual effect of a Post-Earthquake Fire (PEF) stands as a major hassle to designers and rescuers alike. Algerian seismic design code, RPA99v2003, with no exception does not consider the possibility of a subsequent fire after an earthquake, whose effect can significantly weaken the steel frame and destroy its fire protection. This paper presents the evaluation of the fire resistance for a two-storey steel portal frame, damaged by an earthquake simulated through spectrum response of Chlef, scaled three in the Algerian Seismic Code. First, the design of the steel structure considers seismic actions by a static nonlinear analysis. Second, it is followed by a fire analysis using an ISO834 standard fire model, considering that the structure is partially damaged. The finite element simulation and numerical analysis of the structure in post-earthquake fire condition yield the bilinear capacity curve at ambient temperature and the variation of local and global displacement at high temperature. A final comparison of the damaged (PEF) and undamaged (FIRE) frames subjected to the different fire scenarios is done.